2022
DOI: 10.1136/bmjopen-2021-054768
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, views and practices regarding antibiotic prescribing and stewardship among hospital physicians in Jakarta, Indonesia: a questionnaire-based survey

Abstract: ObjectivesAntibiotic overuse is one of the main drivers of antimicrobial resistance (AMR), especially in low-income and middle-income countries. This study aimed to understand the perceptions and views towards AMR, antibiotic prescribing practice and antimicrobial stewardship (AMS) among hospital physicians in Jakarta, Indonesia.DesignCross-sectional, self-administered questionnaire-based survey, with descriptive statistics, exploratory factor analysis (EFA) to identify distinct underlying constructs in the da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers. The ‘Others’ category included challenges like incomplete electronic medical records (EMR), long waiting times for tests, overcrowding in wards [ 30 , 46 ], the perception of AMR as an ‘external problem’ [ 49 ], frequent staff turnover, lack of specific ASP goals [ 36 ], stock shortage of antimicrobials [ 35 ], and suboptimal salary [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers. The ‘Others’ category included challenges like incomplete electronic medical records (EMR), long waiting times for tests, overcrowding in wards [ 30 , 46 ], the perception of AMR as an ‘external problem’ [ 49 ], frequent staff turnover, lack of specific ASP goals [ 36 ], stock shortage of antimicrobials [ 35 ], and suboptimal salary [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…correct dose, diagnosis, and duration of antibiotic) [ 50 – 52 , 59 ]. In terms of attitude towards ASP implementation, the majority of prescribers showed positive attitudes, as they felt ASP is beneficial for both prescribers and patients [ 27 , 29 , 31 , 45 , 49 , 51 , 52 , 60 , 61 ], and were interested receive feedback on their antibiotic prescriptions [ 27 , 31 , 45 , 52 ]. However, some studies also revealed the physicians’ concern that implementation of ASP would limit their prescribing autonomy [ 47 , 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…al . 35 reported these factors include insufficient application of antimicrobial stewardship principles and microbiology services, the lack of confidence in prescribing decisions, and defensive prescribing due to diagnostics uncertainties, fear of patient deterioration, or because the patient insisted. A wide variation exists between hospitals, departments, work experience and medical hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…(11,12) One study demonstrated that prescribers' confidence did not seem to be correlated with their knowledge of judicious antibiotic prescribing (12). Other studies demonstrated similar challenges regarding perception of AR and antimicrobial prescribing despite cultural and contextual differences (20,21) This study aimed to understand the culture of antimicrobial prescribing in order to optimize local strategies regarding antimicrobial stewardship at university hospitals in a Canadian context. The objectives were to assess knowledge, attitudes, and practices amongst antimicrobial prescribers.…”
Section: Survey Instrumentmentioning
confidence: 99%